Wear and friction behaviour of TiAl matrix self-lubricating composites filled with WS2, MoO3 or multilayer graphene. Issue 113 (2nd November 2015) - Xu, Zengshi; Zhang, Qiaoxin; Zhai, Wenzheng
Abstract : FESEM micrographs of cross-sections of worn surfaces of TiAl matrix self-lubricating composites filled with WS2 (a), MoO3 (b) or multilayer graphene (c). Abstract : To further understand the lubrication effects and mechanisms of lamellar solid lubricants, wear and friction behaviours of TiAl matrix self-lubricating composites (TMSC) filled with WS2, MoO3 or multilayer graphene (MLG) are comparatively investigated under different counterface materials. Tribological results indicate that wear and friction properties of TMSC are significantly improved by adding WS2, MoO3 or MLG. Specifically, TMSC filled with MoO3 (TM) have lower friction coefficients and wear rates than TMSC filled with WS2 (TW), while TMSC filled with MLG (TG) have the lowest friction coefficients and wear rates. Meanwhile, EPMA, AFM and FESEM analyses present significant differences in worn surfaces of TMSC. Definitely, the worn surfaces of TM exhibit lighter damage and comparatively more compact films than those of TW; in contrast, the worn surfaces of TG exhibit the lightest damage and the most compact films. It can be concluded that WS2, MoO3 and MLG actually possess different lubrication effects and mechanisms.